Failure analysis on bogie frame with fatigue cracks caused by hunting instability. (October 2021) - Qu, Sheng; Wang, Jianbin; Zhang, Dafu; Li, Dadi; Wei, Lai
Highlights: Early failures on 27 bogie frames were found during maintenance. Field test, extensive investigation, disassemble bogie for inspection were conducted. This kind of cracks were caused by hunting instability. Simulation was carried out to validate the hunting causing mechanism. Solutions were proposed to solve this problem. Abstract: Bogie frame is an important part of rail vehicle, and fatigue cracks impose highly adverse impacts on the running safety. Through field test, extensive investigation and simulation, the cause of early failure of bogie frame is analyzed. The research shows that the bogie hunting instability will affect the stress distribution of the bogie frame, and even lead to the cracking of bogie frame. Because the equivalent conicity of wheelset and clearance of primary suspension will affect the critical speed of the train, the bogie hunting instability occurs when the critical speed is lower than the vehicle running speed. The wheel should be reprofiled regularly and the locating rubber sleeve should be replaced to avoid the hunting instability of the train.